Fixing Accessibility Issues in Open-Source Teaching Repositories - Díaz, Francisco Javier (2017)
In the LINTI, New Information Technologies Research Laboratory at the Computer Science School, in the National University of La Plata, it is being developed a project that involves the integration of the repository, implemented using DSpace, with different tools and platforms used in academic tasks. Accessibility is a process that cuts across all software development stages, so when using a free software product it is important to evaluate it in order to correct faults if it´s necessary. This article describes a DSpace repository accessibility validation, using screen readers for manual test, automatic validation with software tools and experimental test with users with and without disabilities. The evaluation involves the proper basic functions and the implemented extensions. The original DSpace software was extended through the integration with different tools and platforms, such as Moodle LMS, the library management system called Meran, file management services like DropBox and GoogleDrive and the social network Facebook. The tools used during accessibility evaluation were Examinator, Google ChromeVox and one entirely implemented in the LINTI, called SiMor. The experimental tests were made with blind and deaf persons, most of them college students. All the validation results are detailed using tables and graphs, where it can observe the measured values. It is also described the changes that was necessary to carry out in the repository to improve the user experience and ensure Web service accessibility.